KONTRIBUSI TENAGA KERJA WANITA TERHADAP PENDAPATAN KELUARGA (Divisi Bawang Goreng â€œGaruda Jayaâ€pada CV. Duta Agro Lestari) - Valdo Davy Pandean; Melissa L.G. Tarore; Noortje M. Benu (Journal of Agribusiness and Rural Development (Jurnal Agribisnis dan Pengembangan Pedesaan), 2019)
This research was conducted for 4 months starting from February to June 2019. The data used in this study are primary data and secondary data. Primary data obtained from direct interviews with the general manager of CV. Ambassador Agro Lestari uses a questionnaire. Secondary data was obtained from the company, Central Sulawesi Province Central Bureau of Statistics, books, internet, scientific journals and other university theses related to this study mainly involved Income Contributions. The research results showed that the contribution of women worker to family income was 25.87%. This means that the income contribution of Garuda Jaya fried onion business workers to family income in South Tatura Village is in the good category, meaning that the income earned by workers working in fried onion businesses can help families toÂ Â  fulfill their daily needs and contribute real effect on family income. The average time spent by workers on fried onion business in the research area in one day for domestic activities was 5.4 hours per day with a percentage of 22.5%, while the time spent on productive activities was 6.6 hours per day with a percentage of 27, 5% and time for other activities besides taking care of family and working on average was 13 hours per day with a percentage of 54.17%.Keywords: Contribution of women worker, Family Income, CV Duta Agro Lestari